VARIATION OF ACID VALUES IN FLOODPLAIN SOILS OF THE AMUR RIVER - A. V. Martynov (Бюллетень Почвенного института им. В.В. Докучаева, 2019)
Understanding the variability of acidic properties in the soil cover of floodplains is of greatest importance as far as it helps to ensure the rational management of floodplain areas, since the pH level is a fundamental indicator that determines the concentration of soluble and available elements for plants. This article provides the results of actual, potential and exchangeable acidity measurements performed in 87 soil profiles located within the upper and middle reaches of the Amur River. Descriptive statistics, correlation and linear regression were used to characterize acidity. It has been established that acidity decreases in the floodplain of the upper and middle reaches of the Amur River in the following direction: alluvial marsh (peat-gley and humus-gley) soils, residually-alluvial (rzhavozems and brunezems) soils, alluvial gray gley soil, alluvial gray humus. The soils of the upper Amur floodplain are more acidic in comparison with the soils of the middle Amur, the average pHKCl values in soils with the same genesis of the former are less by 0.2–0.4 than the ones of the latter. It was revealed that the regression coefficient is indicative of the acid-base functional groups of the soil components which are in charge of soil pH. The coefficient greater than 1 points to the organic nature of acidity; below 1 – to the prevalence of mineral acids.